1997
DOI: 10.1046/j.1365-3180.1997.d01-58.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weather on the efficacy of dichlorprop‐P/MCPA and trihenuron‐methyl

Abstract: Summary The influence of weather on the efficacy of dichlorprop‐P/MCPA and tribenuron‐methyl on annual weeds in spritig barley was studied in the field during 4 years at six locations in southern Sweden. The herbicides were applied at one‐eighth to three‐quarters of the full dose at three application times with approximately 6‐day intervals. Weather stations, placed in the experiments, recorded climatic data, Maximum herbicide efficacy was obtained when spraying 1 week after the cotyledon stage with half or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 3 publications
1
16
0
2
Order By: Relevance
“…The conclusions will need to be validated in field experiments before commercial adoption, but we expect the findings to be conservative as differences of herbicide activity in growth cabinet studies are often less pronounced than in the field ( Merritt, 1984; Nalewaja & Woznica, 1985). Certainly field experiments by Minkey & Moore (1996) and Lundkvist (1997) conducted over three seasons both found an order of magnitude range in the effective herbicide rate required to achieve weed control, which they attributed to variation in seasonal climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusions will need to be validated in field experiments before commercial adoption, but we expect the findings to be conservative as differences of herbicide activity in growth cabinet studies are often less pronounced than in the field ( Merritt, 1984; Nalewaja & Woznica, 1985). Certainly field experiments by Minkey & Moore (1996) and Lundkvist (1997) conducted over three seasons both found an order of magnitude range in the effective herbicide rate required to achieve weed control, which they attributed to variation in seasonal climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…More effective targeting of dose is a method of reducing the amount of herbicide used while maintaining the level of weed control. It has been shown that, for some herbicides, weather can significantly affect the level of activity ( Hallgren, 1989; Minkey & Moore, 1996; Lundkvist, 1997) and temperature, in particular, has been identified as an important climatic factor affecting herbicide activity ( Caseley, 1987). Controlled environment experiments have demonstrated a strong influence of temperature on the activity of many herbicides including MCPA+dichlorprop ( Jensen & Kudsk, 1988; Kudsk & Kristensen, 1992), chlorsulfuron ( Nalewaja & Woznica, 1985), thifensulfuron ( Kudsk et al ., 1990 ) and ioxynil ( Merritt, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It was not possible to standardise radiation and humidity completely during the trial period. A certain influence of these factors on sulfonylurea performance is reported,26, 27 and may have contributed to the variation observed.…”
Section: Discussionmentioning
confidence: 91%
“…De fato, é complexo o entendimento do melhor horário de aplicação e das causas que afetam a eficá-cia dos produtos em campo, em comparação com experimentos realizados com condições controladas (Lundkvist, 1997;Skuterud et al, 1998;Fornarolli et al, 1999;Fausey & Renner, 2001;Penckoswi et al, 2003;Sellers et al, 2003;Cieslik, 2012).…”
Section: Luminosidadeunclassified
“…Especialmente no verão, com o decorrer do dia a radiação global e a temperatura do ar se elevam e a umidade relativa do ar diminui (Lundkvist, 1997;Skuterud et al, 1998;Cieslik, 2012). Em razão dessas interações, deve-se atentar para uma condição de aplicação na qual o conjunto das variáveis ambientais seja favorável a um maior desempenho do herbicida nas plantas daninhas.…”
Section: Luminosidadeunclassified